Michal Smetana: Nuclear Deviance. Stigma Politics and the Rules of the Nonproliferation Game. - Tůma, Miroslav (Czech Journal of International Relations, 2020)
This book examines the linkage between deviance and norm change in international politics. It draws on an original theoretical perspective grounded in the sociology of deviance to study the violations of norms and rules in the global nuclear non-proliferation regime. As such, this project provides a unique conceptual framework and applies it to highly salient issues in the contemporary international security environment. The theoretical/conceptual chapters are accompanied by three extensive case. studies: Iran, North Korea, and India